Review: Climate change and the water footprint of wheat production in Zimbabwe - Govere, Simbarashe; Nyamangara, Justice; Nyakatawa, Emerson Z (Water SA, 2019)
Reductions in the water footprint (WF) of crop production, that is, increasing crop water productivity (CWP), is touted as a universal panacea to meet future food demands in the context of global water scarcity. However, efforts to reduce the WF of crop production may be curtailed by the effects of climate change. This study reviewed the impacts of climate change on the WF of wheat production in Zimbabwe with the aim of identifying research gaps. Results of the review revealed limited local studies on the impacts of climate change on the WF of wheat production within Zimbabwe. Despite this, relevant global and regional studies suggest that climate change will likely result in a higher WF in Zimbabwe as well as at the global and regional level. These impacts will be due to reductions in wheat yields and increases in crop water requirements due to high temperatures, despite the CO2 fertilization effect. The implications of a higher WF of wheat production under future climate change scenarios in Zimbabwe may not be sustainable given the semi-arid status of the country. The study reviewed crop-level climate change adaptation strategies that might be implemented to lower the WF of wheat production in Zimbabwe.